2020
DOI: 10.1016/j.plantsci.2019.110297
|View full text |Cite
|
Sign up to set email alerts
|

Maize, sorghum, and pearl millet have highly contrasting species strategies to adapt to water stress and climate change-like conditions

Abstract: This study compared maize, sorghum and pearl-millet, leading C 4 cereals, for the transpiration rate (TR) response to increasing atmospheric and soil water stress. The TR response to transiently increasing VPD (0.9-4.1 kPa) and the transpiration and leaf area expansion response to progressive soil drying were measured in controlled conditions at early vegetative stage in 10-16 genotypes of each species grown in moderate or high vapor pressure deficit (VPD) conditions. Maize grown under moderate VPD conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 60 publications
3
30
0
Order By: Relevance
“…1f). The FTSW values achieved in WS1 and WS2 were similar to the critical values (~0.2-0.5) for decreases in transpiration and leaf expansion in diverse sorghum lines (Choudhary et al, 2020), suggesting that a physiologically-relevant stress was experienced by the plants. Second, we observed a substantial (but not complete) reduction of yield components (~50%; Fig.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…1f). The FTSW values achieved in WS1 and WS2 were similar to the critical values (~0.2-0.5) for decreases in transpiration and leaf expansion in diverse sorghum lines (Choudhary et al, 2020), suggesting that a physiologically-relevant stress was experienced by the plants. Second, we observed a substantial (but not complete) reduction of yield components (~50%; Fig.…”
Section: Discussionsupporting
confidence: 62%
“…In this study we sought to better understand genetics of drought adaptation in sorghum, a crop that is well known for drought tolerance, but whose mechanisms of drought adaptation are not yet understood (Choudhary et al, 2020). We characterized a diverse panel of West African sorghum germplasm in common-garden managed drought stress field trials with the aim of balancing experimental repeatability (via the use of irrigation in off-season) with biological and breeding relevance (via the use of a field environment) (Cooper et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…One explanation could be that there are differences between the species in the capacity to restrict transpiration under high VPD that would lead to differences in TE (see Vadez et al , 2014 for a review). Indeed, a recent study investigating water-conserving traits in the same genotypes of maize, sorghum, and pearl millet that we used showed that all three species were able to restrict transpiration under such conditions, although to a much larger extent in maize than in sorghum and pearl millet ( Choudhary et al , 2020 ). Since most of the pearl millet and sorghum material used in our study lacked transpiration sensitivity to high VPD compared to the maize genotypes, they would have lower TE, as previously hypothesized by Sinclair et al (2005) .…”
Section: Discussionmentioning
confidence: 97%
“…The warmer temperatures may result in a faster accumulation of heat units and a reduction in growth duration and accumulation of photosynthesis and increase in night-time respiration, all resulting in reduced crop yield (Schlenker and Roberts, 2009). Unlike bambara groundnut (C3 plant), maize (C4 plant) generally originates from warmer climates (Leff et al, 2004;Jia et al, 2016) and thus, may be more resilient to projected increases of temperature (Choudhary et al, 2019). Then again, for bambara groundnut, optimum temperatures range between 28 and 35 • C and the lethal temperature has been reported to be 50 • C (Soni et al, 2015).…”
Section: Change In Climate During the Growing Seasonmentioning
confidence: 99%